(untitled) (Scientific journal of the Fergana State University, 2025)
This article talks about the wheat (wheat) plant, which is the most basic food base of mankind. Grain is one of the most severely, sometimes very strongly affected plants with many different diseases and pests. To date, more than 50 species of various pests have been observed in the grain fields of the Republic. The article also provides information on the biological properties of pests, living conditions, damage and control measures, on the basis of which chemical control measures against insects in grain are described.